PROMISING DIRECTIONS OF AGRICULTURAL PRODUCTION IN UZBEKISTAN - Siddikov Zahid Tulkunovich (Journals Park Publishing, 2025)
The article discusses promising areas of agricultural production in Uzbekistan. One of the promising areas of agricultural production is the implementation of comprehensive work on the creation of environmentally friendly agricultural products.
Keywords: Agriculture, peasant farms, food industry, product, efficiency, cost of production, gross income, net income.